Cryptococcus neoformans glucuronoxylomannan fractions of different molecular masses are functionally distinct. (February 2014) - Albuquerque, Priscila C; Fonseca, Fernanda L; Dutra, Fabianno F; Bozza, Marcelo T; Frases, Susana; Casadevall, Arturo; Rodrigues, Marcio L
ABSTRACT: : Aims: Glucuronoxylomannan (GXM) is the major polysaccharide component of Cryptococcus neoformans . We evaluated in this study whether GXM fractions of different molecular masses were functionally distinct.Materials & methods: GXM samples isolated from C. neoformans cultures were fractionated to generate polysaccharide preparations differing in molecular mass. These fractions were used in experiments focused on the association of GXM with cell wall components of C. neoformans, as well as on the interaction of the polysaccharide with host cells.Results & conclusion: GXM fractions of variable molecular masses bound to the surface of a C. neoformans acapsular mutant in a punctate pattern that is in contrast to the usual annular pattern of surface coating observed when GXM samples containing the full molecular mass range were used. The polysaccharide samples were also significantly different in their ability to stimulate cytokine production by host cells. Our findings indicate that GXM fractions are functionally distinct depending on their mass.